Adventure Sports, a proposal for personal growth and the development of environmental attitudes - Idalmis Fernández-Téllez; Hirbins Manuel Dopico-Pérez; Abel Baza-Farjat (Universidad de Guantánamo, 2016)
The paper presents a group of terms and definitions that addresses adventure sports in Cuba and shows a study carried out that aimed at evaluating the preferences of the practitioners of adventure sports; it was monitored the choice of practicing this activity in conditions of challenge following the laws of nature, in a privileged situation in regard to other recreational practices, besides it allows to regulate the behavior at difficult situations outdoors and to enjoy it, to take care of it and appreciate it better. For this study, the following indicators were taken into account in the practitioners: knowledge of the activity, need to demonstrate competence, challenge, difficulties, eagerness to achieve success, feelings of dependency in their own strength, knowledge of their physical and mental limits; With the application of methods and techniques of scientific research, results were obtained that demonstrate that this activity is of interest to young people, adolescents and adults, which can be better exploited in different parts of the country and by foreign participants who like this activity.